Enabling PHP software engineering research in Rascal - Hills, Mark; Klint, Paul; Vinju, Jurgen J. (Science of computer programming, 2017)
Today, PHP is one of the most popular programming languages, and is commonly used in the open source community and in industry to build large application frameworks and web applications. In this paper, we discuss our ongoing work on PHP AiR, a framework for PHP Analysis in Rascal. PHP AiR is focused especially on program analysis and empirical software engineering, and is being used actively and effectively in work on evaluating PHP feature usage and system evolution, on program analysis for refactoring and security validation, and on source code metrics. We describe the requirements and design decisions for PHP AiR, summarize current research using PHP AiR, discuss lessons learned, and briefly sketch future work. •We describe a framework in Rascal for PHP software engineering research, PHP AiR.•We report results of using PHP AiR for empirical studies and program analysis.•We examine the design decisions and tradeoffs encountered building PHP AiR.